Akt1 is essential for postnatal mammary gland development, function, and the expression of Btn1a1. - Jessica LaRocca; Jodie Pietruska; Mary Hixon (PLoS ONE)
Akt1, a serine-threonine protein kinase member of the PKB/Akt gene family, plays critical roles in the regulation of multiple cellular processes, and has previously been implicated in lactation and breast cancer development. In this study, we utilized Akt1+/+ and Akt1-/- C57/Bl6 female mice to assess the role that Akt1 plays in normal mammary gland postnatal development and function. We examined postnatal morphology at multiple time points, and analyzed gene and protein expression changes that persist into adulthood. Akt1 deficiency resulted in several mammary gland developmental defects, including ductal outgrowth and defective terminal end bud formation. Adult Akt1-/- mammary gland composition remained altered, exhibiting fewer alveolar buds coupled with increased epithelial cell apoptosis. Microarray analysis revealed that Akt1 deficiency altered expression of genes involved in numerous biological processes in the mammary gland, including organismal development, cell death, and tissue morphology. Of particular importance, a significant decrease in expression of Btn1a1, a gene involved in milk lipid secretion, was observed in Akt1-/- mammary glands. Additionally, pseudopregnant Akt1-/- females failed to induce Btn1a1 expression in response to hormonal stimulation compared to their wild-type counterparts. Retroviral-mediated shRNA knockdown of Akt1 and Btn1a1 in MCF-7 human breast epithelial further illustrated the importance of Akt1 in mammary epithelial cell proliferation, as well as in the regulation of Btn1a1 and subsequent expression of ß-casein, a gene that encodes for milk protein. Overall these findings provide mechanistic insight into the role of Akt1 in mammary morphogenesis and function.